2011
DOI: 10.1007/s00497-011-0178-8
|View full text |Cite
|
Sign up to set email alerts
|

Wide-scale screening of T-DNA lines for transcription factor genes affecting male gametophyte development in Arabidopsis

Abstract: Male gametophyte development leading to the formation of a mature pollen grain is precisely controlled at various levels, including transcriptional, post-transcriptional and post-translational, during its whole progression. Transcriptomic studies exploiting genome-wide microarray technologies revealed the uniqueness of pollen transcriptome and the dynamics of early and late successive global gene expression programs. However, the knowledge of transcription regulation is still very limited. In this study, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 142 publications
2
28
0
2
Order By: Relevance
“…6). Consistent with the current results, the expression of DAF1 , PCR11 , TIP5;1 , ATTLP6 , and ACA9 is more pronounced after the tetrad stage when ASKβ expression is strong, and altering the expression of these genes also causes abnormal microgametogenesis (Borg et al, 2011; Reňák et al, 2012; Schiott et al, 2004; Soto et al, 2010). ASK β may activate regulatory protein(s) that transcriptionally induce the expression of these genes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…6). Consistent with the current results, the expression of DAF1 , PCR11 , TIP5;1 , ATTLP6 , and ACA9 is more pronounced after the tetrad stage when ASKβ expression is strong, and altering the expression of these genes also causes abnormal microgametogenesis (Borg et al, 2011; Reňák et al, 2012; Schiott et al, 2004; Soto et al, 2010). ASK β may activate regulatory protein(s) that transcriptionally induce the expression of these genes.…”
Section: Discussionsupporting
confidence: 91%
“…Six ASKβ co-expressed and TDF1 -regulated genes can be categorized by their putative functions or expression characteristic, as summarized in Table 1. Knock-out of BCP1 and ATTLP6 mutations leads to cytoplasmic degradation and defects in late pollen development, respectively (Reňák et al, 2012; Xu et al, 1995). While DAF1 , PCR11 , and TIP5;1 are involved in sperm cell formation (Borg et al, 2011), ACC9 is important for fertility and mutation in ACC9 results in more than 80% reduction of seed set (Schiott et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most (58.6%) belonged to six families: MYB, WRKY, NAC, C2C2-CO-like, bHLH, and AP2-EREBP (Figure 5A, Additional file 8A). Expression and genetic analyses have substantiated the involvement of all six TF families in flower development and reproduction [21-24]. It is unclear, however, whether these TFs are directly involved in pollen-stigma interaction.…”
Section: Resultsmentioning
confidence: 99%
“…These components are vital for the normal development of anthers, microspore/pollen formation, and pollen wall formation (Li et al 2006Parish and Li 2010;Shi et al 2011;Clements et al 2012). Reňák et al (2012) have reported that mutations of two tapetum-expressed genes, TAZ1 and MEZ1, can cause aberrant meiosis and pollen abortion, and can trigger the process of programmed cell death in Petunia hybrida. In the fertile wild type plants of T. patula, the binucleate microspore progressed to become a trinucle at pollen grain surrounded by the periplasmodial tapetum.…”
Section: Discussionmentioning
confidence: 99%